Advantages of Chemical Exchange-Sensitive Spin-Lock (CESL) Over Saturation Transfer (CEST) for Hydroxyl- and Amine-Water Proton Exchange Studies - Jin, Tao (2014)
The chemical exchange (CE) rate of endogenous hydroxyl and amine protons with water is often comparable to the difference in their chemical shifts. These intermediate exchange (IMEX) processes have been imaged by the CE saturation transfer (CEST) approach with low-power and long-duration irradiation. However, its sensitivity is not optimal, and more importantly, the signal is contaminated by slow magnetization transfer processes. Here, the property of CEST signals is compared to a CE-sensitive spin-locking (CESL) technique irradiating at the labile proton frequency. Firstly, using a higher power and shorter irradiation in CE-MRI yields i) increasing selectivity to faster chemical exchange rates by higher sensitivity to faster exchanges and less sensitivity to slower CE and magnetization transfer processes, and ii) decreasing in vivo asymmetric magnetization transfer contrast measured at ±15 ppm. The sensitivity gain of CESL over CEST is higher for a higher-power and shorter irradiation. Unlike CESL, CEST signals oscillate at a very high power and short irradiation. Secondly, time-dependent CEST and CESL signals are well modeled by analytical solutions of CE-MRI with asymmetric population approximation (CEAPA), which can be used for quantitative CE-MRI, and validated by simulations of Bloch-McConnell equations and phantom experiments. Lastly, in vivo amine-water proton exchange contrast measured at 2.5 ppm with ω(1) of 500 Hz is 18% higher in sensitivity for CESL than CEST at 9.4 T. Overall, CESL provides better exchange rate selectivity and sensitivity than CEST; therefore, CESL is more suitable for CE-MRI of IMEX protons.